A continental shelf sedimentary record of Little Ice Age to modern glacial dynamics: Bering Glacier, Alaska - Jaeger, John M.; Kramer, Branden (Continental Shelf Research, 2014)
The Bering Glacier System is the world's largest surging temperate glacier with seven events occurring over the past century under a range of north Pacific climatic conditions. Onshore records reveal changes in glacial termini positions and evidence of late Holocene glacial advances, but the Little Ice Age (LIA) record of potential glacial surging and associated flooding has not been examined. A 13.6 m-long jumbo core collected on the adjacent continental shelf reveals a 600-yr-long record of sedimentation associated with changing glacifluvial discharge. The chronology is based on 210Pb geochronology and five radiocarbon dates, and the core can be separated into three distinct lithologic units based on the examination of X-radiographs and physical properties: (1) an uppermost unit dating from ∼125 cal yr BP to the present characterized by bioturbated mud interbedded with laminated, thick (5–20 cm) low-bulk density clay-rich beds; (2) a middle unit dating from ∼120–400 cal yr BP that includes numerous interlaminated-to-interbedded low- and high-bulk density beds with infrequent evidence of bioturbation; thick laminated clay-rich beds are rare; (3) a lowermost unit that predates ∼400 cal yr BP and is composed of rare laminated beds grading down into mottled to massive mud. In each of these units, the laminated lithofacies from this mid-shelf location indicates both flood deposition and likely sediment transport in the wave-current bottom-boundary layer. The thick low-density, clay-rich beds in the uppermost unit correlate with historic outburst floods associated with known surge events. Based on previous terrestrial studies, the terminus was at its Holocene Neoglacial maximum extent close to the modern coastline at some point in the middle to late stages of the LIA in southern Alaska (100–350 cal yr BP). During the LIA, preservation of bioturbated intervals is rare while laminated intervals are common. This style of interbedding indicates frequent (
id: 2324